Investigation on Self-Assembled InAs Quantum dots embedded in GaAs p-i-n active region for photovoltaic cell application - Molleda, Hazel D. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2010)
A baseline for solar cell technology was implemented at the Condensed Matter Physics Laboratory of the National Institute of Physics by incorporating InAs qantum dots (QDs) to the GaAs-based p-i-n layer. Three QD samples of different sizes were grown and characterized optically before inserting in the active region of p-i-n layer. Room temperature photoluminescence measurements confirmed the presence of optically active QDs and their tunable absorption to longer wavelengths. Room temperature photocurrent measurements at zero bias showed a broad peak response of QDs in the infrared region ranging from 9000-12000 A. External quantum efficiency (EQE) of 2.9% for p-i-n with dots showed hgher collection efficiency as compared to 0.33% EQE of the reference bulk layer. Voc and ISC values of 0.38V and 43.36mA/cm2 for p-i-n with dots wih fill factor (FF) of 34% gives a maximum ower density output of 5.5 W/cm2 which is an improvement for 2.4 mW/cm2 of AlGaAs bulk device